ANALISA IMPLEMENTASI RATIFIKASI EUROPEAN COUNCIL REGULATION 1005/2008 DALAM MENINGKATKAN SERTIFIKASI HASIL TANGKAP IKAN TUJUAN EKSPOR (STUDI KASUS PELABUHAN PERIKANAN NIZAM ZACHMAN PERIODE 2019-2021) - Lisda Yulia (2023)
Catch fish commodities in Indonesia are considered capable of supporting economic growth through fisheries trade, but from a governance perspective, catch fish are still constrained by internal and external constraints, resulting in low fish catch certification. The purpose of this study is to analyze the implementation of the ratification of the European Council regulation 1005/2008 as an effort to increase the certification of catch fish and support the expansion of the Indonesian fish export market. This study is included in the focus of International Business studies, therefore the authors use the concept of international cooperation to analyze the implementation of ratification of international law ECR 1005/2008 in Indonesia and use international trade theory of competitive advantage to analyze indicators of perfect trade in catch fish commodities at research locus. The author uses a qualitative research method with a single case study approach to the implementation of ECR 1005/2008 at PPS Nizam Zachman for the 2019-2021 period, so that in-depth results are obtained. This study shows that the implementation of ECR 1005/2008 in PPS Nizam Zachman is able to increase the certification of catch fish obtained by prioritizing the synergy between the European Council, Fishing Port, and Fish Processing Units. However, in order to increase the export value, deeper awareness is needed from the human resources of the crew/fisherman in the proper way of handling fish, to maintain the trust of buyers in importing countries.